Synthesis of Novel Pyrazolyl-1, 3, 4-Thiadiazole Analogues. (21st April 2022) - Ningaiah, Srikantamurthy; Bhadraiah, Umesha K.; Sobha, Anjali; Shridevi, Doddamani
Abstract: In the present study, we have designed a novel series of pyrazolyl-1, 3, 4-thiadiazole analogues by accommodating 1, 3, 4-thiadiazole ring at C – 4 of pyrazole ring with and without an amide linkage; 5-methyl-1, 3-diphenyl- N -(5-phenyl-1, 3, 4-thiadiazol-2-yl)-1 H -pyrazole-4-carboxamide and 2-(5-methyl-1, 3-diphenyl-1 H -pyrazol-4-yl)-5-phenyl-1, 3, 4-thiadiazole respectively. We have designed this class of heterocycles by keeping a wide audience in mind, which augment their scientific knowledge. Newly synthesized compounds were characterized by 1 H NMR, 13 C NMR, mass, IR spectral studies. Single crystal X-ray analysis of some compounds also gave insight into the structural information. Graphical Abstract: